GaN-HEMT Based Test Setup for Measurement of Core Losses Under DC-Bias - Kohlhepp, Benedikt; Kübrich, Daniel; Dürbaum, Thomas (ETG-Fachbericht, 2022)
For power electronics designers, accurate magnetic core loss predictions play a major role in converter design and optimization. Unfortunately, loss predictions are still a difficult task, since manufacturers do not provide enough information in their data sheets for the many parameters affecting the losses. Especially, core loss results under DC-bias of the flux density are missing. Thus, this paper presents a method for these core loss measurements. Instead of using the most common AC metering approach, this paper relies on a DC current and voltage measurement at the input of the inductor loss test setup. After introducing the test setup and its operation principle, the instrumentation and its requirements is studied. Measurements with a device under test deliver the core losses under DC-bias, which show an increase of losses of 13% due to DC-bias in flux density. These results demonstrate the necessity to perform core loss measurement under DC-bias.
CRIS-Team Scopus Importer:2022-09-02